Passar la vita a Diol Kadd: Gianni Celati’s ‘out of place’ Africa (Altre Modernità, 2024)
Passar la vita a Diol Kadd by Gianni Celati is a double and ‘transmedial’ work, consisting of a book and a film, which tells in words and images the long experience of the writer in a Senegalese village, where from 2003 to 2006 he went several times to prepare the staging of a comedy by Aristophanes, Ploutos. The revisitation, carried out in collaboration with a local actor and the active participation of the entire community, will be filmed and projected on a screen mounted in the savannah, according to a collective working criterion that recalls the logic of artivism. Celati recounts this undertaking – carried out through a series of complications and incidents, both inside and outside the theatrical ‘frame’ – establishing a mode of story-telling that is not configured neither as documentary nor as odeporic. In each of its ‘halves’, Passar la vita a Diol Kadd is a story of observation of the flowing life, a writing of contemplation that bypasses the distortive mechanisms of fiction moving away from the myths, limits and distortions of Western ethnocentrism.
Keywords: Africa; West; Aristophanes; Ploutos; richness; poverty; mouridism